IL-6 And IL-8 Levels In Patients With Acute Exacerbation Of Chronic Obstructive Pulmonary Disease - Akbulut, H. H.; Ozden, M.; Deveci, F.; Muz, M. H. (Premchand Shantidevi Research Foundation, 2009)
Background: Chronic Obstructive Pulmonary Disease (COPD) is characterized by an abnormal inflammatory response of airways due to inhalation of harmful gases and particles. Frequent exacerbations are associated with increased pulmonary and systemic inflammation. Interleukin-6 (IL-6) and interleukin-8 (IL-8) are systemic inflammation markers. Aim: The relationship of serum IL-6 and IL-8 levels in patients of exacerbated COPD with pulmonary function tests (PFT), forced expiratory volume in one second (FEV1), FEV1/forced vital capacity (FVC) values, C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR) were studied. Methods and Materials: Twenty-seven patients with exacerbated COPD and 20 healthy controls were included in the study. In addition to acute exacerbation therapy, antibiotics were used in all patients. Results: The mean duration of antibiotic usage was 14.1 +/- 7.3 days and the mean FEV1 value was 34.11 +/- 10.43. Pretreatment and post treatment IL-6 and IL-8 levels were measured by the ELISA method. Pretreatment IL-6 and IL-8 levels were found to be significantly higher in acute excacerbation cases, when compared to levels in the healthy control group and post treatment levels. But no correlation was found between IL-6, IL-8 levels and CRP, ESR values and FEV1, FEV1/FVC values. Conclusion: We conclude that cases of exacerbated COPD with greater degrees of obstruction of the airways have higher levels of cytokines in serum. The serum levels of these cytokines can therefore be utilised as the clinical and prognostic parameters for evaluation of the disease status and the therapy executed for the same.
Keywords: IL-6; IL-8; Chronic obstructive pulmonary disease